2013
DOI: 10.3109/15622975.2013.860467
|View full text |Cite
|
Sign up to set email alerts
|

Decreased whole-blood global DNA methylation is related to serum hormones in anorexia nervosa adolescents

Abstract: A better definition of the epigenetic dysregulation underlying AN pathology or vulnerability might lead to develop useful markers for diagnosis, prognostic classification and tailored therapeutic interventions in these vulnerable patients since the earliest phases of their disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…AN and BN subjects showed increased methylation of dopamine system genes [103]. Taken together, these findings suggest that alterations in DNA methylation can lead to EDs by influencing a wide variety of systems implicated in behavioral/affective regulation, sensitivity to nutritional insufficiencies, and body-weight maintenance [99,104,105]. Genome-wide methylation profiles in women with AN-restrictive type, and women with AN-binge/purge type compared with normal-weight/normal-eater control women, showed higher and less variable global methylation patterns in AN than controls [59].…”
Section: Epigeneticsmentioning
confidence: 75%
“…AN and BN subjects showed increased methylation of dopamine system genes [103]. Taken together, these findings suggest that alterations in DNA methylation can lead to EDs by influencing a wide variety of systems implicated in behavioral/affective regulation, sensitivity to nutritional insufficiencies, and body-weight maintenance [99,104,105]. Genome-wide methylation profiles in women with AN-restrictive type, and women with AN-binge/purge type compared with normal-weight/normal-eater control women, showed higher and less variable global methylation patterns in AN than controls [59].…”
Section: Epigeneticsmentioning
confidence: 75%
“…Epigenetic studies also suffer from power issues as candidate gene studies have in detecting reproducible associations. For example, while Tremolizzo et al (Tremolizzo et al, 2014) identified a modest yet significant reduction of global DNA methylation in AN, Saffrey et al (Saffrey et al, 2014) reported no alterations in global or gene-specific DNA methylation. Yet, a most recent study by Booij et al reported a higher global DNA methylation in AN groups compared to controls (Booij et al, 2015).…”
Section: Alteration Of Gene Expression: Mrna and Methylationmentioning
confidence: 99%
“…Blood samples were collected between 8.00 and 8.30 a.m., following overnight fasting and plasma fractions were immediately obtained, as previously described [13]. Whole blood for DNA extraction and plasma aliquots were stored at -80°C until assay.…”
Section: Methodsmentioning
confidence: 99%
“…Whole blood for DNA extraction and plasma aliquots were stored at -80°C until assay. Hcy determination was performed only in AN patients and blood samples were kept on ice before immediate assay by HPLC at the Laboratory of Analysis of the San Gerardo Hospital that gave reference values as well [13]. Laboratory investigations were carried out blindly with respect to clinical data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation